Right ventricle remodelling: from in vitro to in vivo and from simple to complex models - Paula A. da Costa Martins; Martina Calore; Jordy M.M. Kocken (Journal of Molecular and Cellular Cardiology Plus)
Right ventricle failure (RVF) is a debilitating disease with no cure available. While much is known about the failing left ventricle (LV), many mechanisms and signalling pathways of remodelling are different between the two ventricles. Over the past decades, new insights into the mechanisms of the disease have helped in managing disease progression and improving patient comfort. To study RVF both in vitro and in vivo and even ex vivo, relevant experimental models are required to discover new mechanisms and test novel therapeutic approaches. During the past decades many strategies to mimick RV hypertrophy (RVH), to some extent, have been developed and described with using varying methods of disease induction. Such models either require genetic modulation, surgical intervention, chemical injections, or changes in environmental exposure.As each approach has a different set of requirements of facility and skills, one needs to carefully consider which one better suits a specific study or answer a specific research question. In this review, we provide an overview of the most common in vitro techniques, both 2 and 3 dimensional, in vivo and promising ex vivo approaches to study RV remodelling.